A role for community health promoters in tuberculosis control in the state of Chiapas, Mexico. - Herce, Michael E; Chapman, Jacob A; Castro, Arachu; García-Salyano, Gabriel; Khoshnood, Kaveh (Journal of community health, 2010)
We conducted a qualitative study employing structured interviews with 38 community health workers, known as health promoters, from twelve rural municipalities of Chiapas, Mexico in order to characterize their work and identify aspects of their services that would be applicable to community-based tuberculosis (TB) control programs. Health promoters self-identify as being of Mayan Indian ethnicity. Most are bilingual, speaking Spanish and one of four indigenous Mayan languages native to Chiapas. They volunteer 11 h each week to conduct clinical and public health work in their communities. Over half (53%) work with a botiquín, a medicine cabinet stocked with essential medicines. Fifty-three percent identify TB as a major problem affecting the health of their communities, with one-fifth (21%) of promoters reporting experience caring for patients with known or suspected TB and 29% having attended to patients with hemoptysis. One-third of health promoters have access to antibiotics (32%) and one-half have experience with their administration; 55% complement their biomedical treatments with traditional Mayan medicinal plant therapies in caring for their patients. We describe how health promoters employ both traditional and allopathic medicine to treat the symptoms and diseases they encounter most frequently which include fever, diarrhea, and parasitic infections. We contend that given the complex sociopolitical climate in Chiapas and the state's unwavering TB epidemic and paucity of health care infrastructure in rural areas, efforts to implement comprehensive, community-based TB control would benefit from employing the services of health promoters.
Keywords: Adolescent; Adult; Community Health Planning; Community Health Services; Community Health Workers; Complementary Therapies; Female; Health Knowledge, Attitudes, Practice; Health Promotion; Humans; Interviews as Topic; Male; Medicine, Traditional; Mexico; Middle Aged; Multilingualism; Qualitative Research; Rural Health Services; Tuberculosis; Voluntary Workers; Young Adult